The Mediating Effect Of Innovation Culture In Computerised Accounting Information System (Cais) Implementation Factors Towards Construction Companies Performance In Iraq - Al Hashmy, Hisham Noori Hussain (2023)
The construction industry must implement new technologies, such as computerise accounting information systems (CAIS), to overcome a number of obstacles in order to adapt to the ever-changing construction environment. There is a need to investigate the effect of CAIS contexts on construction companies’ performance and the role of innovation culture as a mediator between CAIS and construction companies’ performance. A thorough evaluation of the literature was done in response to this identified research gap, focusing on the relationship between CAIS and construction companies’ performance. The finding of the literature study showed that CAIS and construction company performance are poorly understood. Empirical research is needed to close this gap and improve CAIS implementation industry practises. This study seeks to investigate the impact of CAIS contexts on the performance of construction companies and the role of innovation culture as a moderator in the relationship between CAIS and performance. The construction companies in Iraq were surveyed for this study using a structured, self-administered questionnaire. From a population of 208 businesses, a non-probability sampling technique was employed, resulting in a 73% response rate. The collected data were analysed to determine the influence of CAIS on the performance of construction companies. The results indicate that none of the three CAIS contexts had a substantial effect on the performance of construction companies.